1986
DOI: 10.1029/ja091ia05p05769
|View full text |Cite
|
Sign up to set email alerts
|

Production of flickering aurora and field‐aligned electron flux by electromagnetic ion cyclotron waves

Abstract: Recent observations have suggested that flickering aurora is produced by a modulation of the field-aligned component of the electron flux within an auroral arc. It is proposed that a portion of the field-aligned electrons are of ionospheric origin and that these electrons are accelerated and their flux modulated by electromagnetic ion cyclotron waves that occur below the main acceleration region on auroral •rc field lines. A model of the electromagnetic ion cyclotron wave shows that the parallel phase velocity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
103
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 135 publications
(114 citation statements)
references
References 79 publications
11
103
0
Order By: Relevance
“…A few observations of such high-energy electrons have been reported based on rocket observations [Spiger and Anderson, 1985;McFadden et al, 1987]. In contrast to previous reports considering that the flickering aurora is originated from EMIC waves inside or below the inverted-V acceleration region [e.g., Temerin et al, 1986], Whiter et al [2010] suggested that the high-energy flickering aurora is explained by the resonance interaction between EMIC waves and precipitating electrons above the inverted-V acceleration region.…”
Section: Introductionmentioning
confidence: 55%
See 4 more Smart Citations
“…A few observations of such high-energy electrons have been reported based on rocket observations [Spiger and Anderson, 1985;McFadden et al, 1987]. In contrast to previous reports considering that the flickering aurora is originated from EMIC waves inside or below the inverted-V acceleration region [e.g., Temerin et al, 1986], Whiter et al [2010] suggested that the high-energy flickering aurora is explained by the resonance interaction between EMIC waves and precipitating electrons above the inverted-V acceleration region.…”
Section: Introductionmentioning
confidence: 55%
“…are the parallel and perpendicular wave number, and w ci is the ion cyclotron frequency, respectively [Temerin et al, 1986, Sakanoi et al, 2005.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations